Determinants of Women's Health Status and Health-Care Utilization in a Developing Country: A Latent Variable Approach - Wolfe, Barbara L.; Behrman, Jere R. (The Review of Economics and Statistics, 1984)
A latent-variable representation of health is used in a system that determines health and various indicators of health and health-care utilization for Nicaraguan women. Estimates differ somewhat from standard estimates. They imply that women's schooling increases health-care utilization, literate women report less disease incidence, women's childhood backgrounds affect their adult health and health-care utilization, and general resources favor childbirth-related care, but women's full income favors general care. The most significant result is that several important characteristics usually associated with development-women's schooling, household resources, and women's labor force participation-have inverse or no associations with women's health. Health status is hypothesized to be important in developing countries, both as a direct indicator of welfare and because of its possible impact on productivity. Health-care utilization also is of interest, both because of its relation to health status and because it is a particular manifestation of demand and supply for a 1 modem service. Work on the determinants of health status and health-care utilization in developing economies, however, is flawed because true health status is not directly observable. The indicators of health status that have been used in empirical studies-anthropometric measures, days ill, self-reported or clinical disease records, inputs such as nutrients, and health-care utilization indicesare imperfect indicators of underlying health status and generally do not give a congruent representation of that status. Thereby they may not measure adequately health status and their use may lead to biases in estimates and incorrect interpretations. We use a latent variable methodology for the first time to explore health status and health-care utilization in a developing country.' This approach employs systematic relations between various indicators of health status and health status itself and between health status and various related outcomes so that it is possible to estimate the determinants of health status and control for health status in other relations, even though health status is not directly observed. By using this methodology we obtain more satisfactory estimates of the determinants of health status and of health-care utilization in a developing country context than previous estimates using direct but imperfect proxies. This should improve the empirical bases for evaluating health and related policies in the developing world. I. Latent Variable Model of Health Status and Health-Care Utilization In the human capital tradition of analysis of health, individual health status is viewed as determined by individual demand factors given supply prices, environment, age and resources (including genes). Health-care utilization is a derived demand for a service which is used to produce better health. To incorporate the latent variable representation of the unobserved health status, we assume that the demand-supply health status and health-care utilization interactions, as well as the relation of other health indicators to health status, can be represented by the following linear system of relations: